Application timing affects the selectivity of herbicides for garlic crops - Guerra, Naiara; Dalla Costa, Gabriel; Coratto Demartini, Samyra; Radzinski, Angela Sofia; Poeta Fermino Junior, Paulo Cesar; Mendes de Oliveira Neto, Antonio (Comunicata Scientiae, 2022)
Chemical control is the main weed control method in garlic crops; however, this crop is sensitive to herbicides, which can cause injuries and decrease yield depending on the products used, application timing, rate, and cultivar. In this context, the objective of this study was to evaluate the selectivity of herbicides for garlic plants (cultivar Chonan), using different application timings. A greenhouse experiment was conducted in a completely randomized design with four replications. An 8×2 factorial arrangement was used, in which the first factor consisted of a control without herbicide and seven herbicides (linuron, diuron, pendimethalin, s-metolachlor, oxyfluorfen, flumioxazin, and oxadiazon) applied according to the second factor, application timings (preemergence or post-emergence). Phytotoxicity, photosynthetic rate, stomata morphometry, bulb diameter, and crop yield of garlic were evaluated. Pre-emergence applications were more selective than post emergence applications. The herbicides linuron, diuron, s-metolachlor, and oxadiazon applied at pre-emergence, and s-metolachlor, oxyfluorfen, flumioxazin, and oxadiazon applied at post-emergence were not selective for the Chonan garlic cultivar. Pendimethalin presented the highest selectivity, regardless of the application timing. Oxyfluorfen and flumioxazin applied at pre-emergence and linuron and diuron applied at post-emergence were selective for the cultivar Chonan.